2005
DOI: 10.1038/sj.ejcn.1602235
|View full text |Cite
|
Sign up to set email alerts
|

Relations between high ponderal index at birth, feeding practices and body mass index in infancy

Abstract: Objective: We compared feeding practices between infants of high ponderal index (PI) at birth (PI above the 90th percentile) and normal PI at birth (PI between 10th and 90th percentiles), and examined how birth size and infant feeding practices were related to body mass index (BMI) at 12 months. Design: In a cohort of 3000 infants invited to participate in a national Norwegian dietary survey, 1825 participated both at 6 and 12 months of age, and the present study included those born full term and with a PI (we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Previous studies have shown that a high ponderal index at birth was associated with lower mortality and hospitalizations in infancy and childhood (Morris et al, 1998). However, a high ponderal index at birth has also been associated with higher BMI in infancy in a study carried out in Norway (Lande et al, 2005) and in the present analyses.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Previous studies have shown that a high ponderal index at birth was associated with lower mortality and hospitalizations in infancy and childhood (Morris et al, 1998). However, a high ponderal index at birth has also been associated with higher BMI in infancy in a study carried out in Norway (Lande et al, 2005) and in the present analyses.…”
Section: Discussionsupporting
confidence: 50%
“…There is also evidence that these variables predict growth during infancy, childhood and adolescence, as well as nutritional status in adulthood (Thorburn and Proietto, 2001;Ong and Dunger, 2002;Samaras et al, 2003;Rogers, 2003). More recently, studies have also addressed the issue of proportionality at birth and its effects on health and nutritional status (Lande et al, 2005;Wells et al, 2005). It was previously shown that birth proportionality was positively associated with breastfeeding duration (Lande et al, 2005) and height at 9 years of age (Wells et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…infants more retarded in weight than in length (Landmann et al 2006). High PI at birth has been associated with a shorter duration of exclusive breastfeeding (Lande et al 2005). We compared feeding practices between infants of high (PI above the 90 th percentile), normal (PI between 10 th and 90 th percentiles) and low PI at birth (PI below the 10 th percentile).…”
Section: Methodsmentioning
confidence: 99%
“…Infants who were part of this research study had an overall decrease in ponderal index from 1 mo [26.77 (2.23) Lande et al (2005). In addition, these infants began to walk independently (defined as 3-5 steps without support) at 12.48 (1.52) mo.…”
Section: Participantsmentioning
confidence: 99%